2020
DOI: 10.3390/pr8030328
|View full text |Cite
|
Sign up to set email alerts
|

Study of Activation Energy on the Movement of Gyrotactic Microorganism in a Magnetized Nanofluids Past a Porous Plate

Abstract: The present study deals with the swimming of gyrotactic microorganisms in a nanofluid past a stretched surface. The combined effects of magnetohydrodynamics and porosity are taken into account. The mathematical modeling is based on momentum, energy, nanoparticle concentration, and microorganisms’ equation. A new computational technique, namely successive local linearization method (SLLM), is used to solve nonlinear coupled differential equations. The SLLM algorithm is smooth to establish and employ because thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(35 citation statements)
references
References 54 publications
1
34
0
Order By: Relevance
“…Furthermore, the skewness level attains an average of 0.0257. It is essential that a lower value of skewness is achieved since it helps to calculate the solution with a higher accuracy percentage [37,38]. Therefore, the generated mesh should have a minimal skewness before proceeding for further analysis [39,40].…”
Section: Parametersmentioning
confidence: 99%
“…Furthermore, the skewness level attains an average of 0.0257. It is essential that a lower value of skewness is achieved since it helps to calculate the solution with a higher accuracy percentage [37,38]. Therefore, the generated mesh should have a minimal skewness before proceeding for further analysis [39,40].…”
Section: Parametersmentioning
confidence: 99%
“…Tripathi et al [39] reported shape effects of nanoparticle on blood flow in a microvascular flow. Bhatti et al [40] have discussed the movement of gyrotactic microorganism in a magnetized nanofluid over a plate. Ibrahim and Anbessa [41] discussed Casson nanofluid with Hall and Ion slip effects.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the shear thinning nature of the nanofluid, we used the power law model for mathematical modeling in the form of shear stress and shear rate relation which obeys the experimental trend. In literature, widespread practice is done by this model in different flow situations [17–37]. Moreover, several shapes of equipments are used in industry for different processes.…”
Section: Introductionmentioning
confidence: 99%